The intersection of cancer, cancer stem cells, and the immune system: therapeutic opportunities - Silver, Daniel J. (Neuro Oncol, 2016)
During brain neoplasia, malignant cells subjugate the immune system to provide an environment that favors tumor growth. These mechanisms capitalize on tumor-promoting functions of various immune cell types and typically result in suppression of tumor immune rejection. Immunotherapy efforts are underway to disrupt these mechanisms and turn the immune system against developing tumors. While many of these therapies are already in early-stage clinical trials, understanding how these therapies impact various tumor cell populations, including self-renewing cancer stem cells, may help to predict their efficacy and clarify their mechanisms of action. Moreover, interrogating the biology of glioma cell, cancer stem cell, and immune cell interactions may provide additional therapeutic targets to leverage against disease progression. In this review, we begin by highlighting a series of investigations into immune cell-mediated tumor promotion that do not parse the tumor into stem and non-stem components. We then take a closer look at the immune-suppressive mechanisms derived specifically from cancer stem cell interactions with the immune system and end with an update on immunotherapy and cancer stem cell-directed clinical trials in glioblastoma.